Cognitive and Affective Perspective-Taking: Evidence for Shared and Dissociable Anatomical Substrates - Healey, Meghan L.; Grossman, Murray (Frontiers in Neurology, 2018)
Perspective-taking refers to the ability to recognize another person’s point of view. Crucial to the development of interpersonal relationships and prosocial behavior, perspective-taking is closely linked to human empathy, and like empathy, perspective-taking is commonly subdivided into cognitive and affective components. While the two components of empathy have been frequently compared, the differences between cognitive and affective perspective-taking have been under-investigated in the cognitive neuroscience literature to date. Here, we define cognitive perspective-taking as the ability to infer an agent’s thoughts or beliefs, and affective perspective-taking as the ability to infer an agent’s feelings or emotions. In this paper, we review data from functional imaging studies in healthy adults as well as behavioral and structural imaging studies in patients with behavioral variant frontotemporal dementia in order to determine if there are distinct neural correlates for cognitive and affective perspective-taking. Data suggest that there are both shared and non-shared cognitive and anatomic substrates. For example, while both types of perspective-taking engage regions such as the temporoparietal junction, precuneus, and temporal poles, only affective perspective-taking engages regions within the limbic system and basal ganglia. Differences are also observed in prefrontal cortex: while affective perspective-taking engages ventromedial prefrontal cortex, cognitive perspective-taking engages dorsomedial prefrontal cortex and dorsolateral prefrontal cortex. To corroborate these findings, we also examine if cognitive and affective perspective-taking share the same relationship with executive functions. While it is clear that affective perspective-taking requires emotional substrates that are less prominent in cognitive perspective-taking, it remains unknown to what extent executive functions (including working memory, mental set switching, and inhibitory control) may contribute to each process. Overall results indicate that cognitive perspective-taking is dependent on executive functioning (particularly mental set switching), while affective perspective-taking is less so. We conclude with a critique of the current literature, with a focus on the different outcome measures used across studies and misconceptions due to imprecise terminology, as well as recommendations for future research.